Effect of the phenolic compounds from Sabara jaboticaba (Plinia jaboticaba (Vell.) Berg) in reducing health risks caused by obesity - Moura, Márcio Hercules Caldas (2020)
Sabara jaboticaba (Plinia jaboticaba (Vell.) Berg) is a Brazilian native fruit from Atlantic Forest, rich in polyphenols and appreciated for consumption both in natura and in various preparations. This study aimed to evaluate whether phenolic compounds of Sabara jaboticaba, in the form of phenolic extract (PEJ), can reduce the health risks caused by obesity and associated health problems induced by a fat-sucrose-rich diet (HFSD) in C57BL/6J mice. Initially, for 14 weeks, 66 8-week-old male mice were randomly distributed into two groups: negative control (CH), fed with standard AIN96M diet and water ad libitum; positive control (HFS), fed with HFSD and water ad libitum. At the end of this stage, 10 animals from each group were euthanized under anesthesia and their organs and tissues collected. The remaining animals were redistributed into four groups for another 14 weeks: group CH, fed a standard diet and water; HFS group, fed with HFSD and water; PEJ1 group, fed with HFSD and PEJ at the dose of 50 mg equivalent of gallic acid (GAE)/kg of body weight (BW); group J100 fed with HFSD and PEJ at the dose of 100 mg GAE/kg BW. Food intake, BW, and fasting blood glucose (FBG) were measured weekly and water (CH and HFS) or PEJ (PEJ1 and PEJ2) were daily administered. In the 26th week the intraperitoneal insulin tolerance test (ipITT) was performed, in the 27th, the oral glucose tolerance test (oGTT), and, in the 28th, the analyzes related to energy homeostasis. At the end of the experiment, the animals were euthanized under anesthesia and their organs and tissues were collected. When compared to the HFS group, animals that received PEJ showed decrease in BW gain of approx. 30% and of approx. 45% in the gain of total white adipose tissues (WAT). In addition, the PEJ groups showed less hypertrophied adipocytes. Inflammation markers were significantly reduced in both treated groups. The FBG was approx. 13% lower for the PEJ groups compared to the HFS group. In addition, the mean values of ipITT, oGTT, insulin and HOMA-IR demonstrated that PEJ increased insulin sensitivity and decreased glucose intolerance. GLUT4 expression in the muscle was also increased in the treated groups. The fecal lipid content was lower in the PEJ groups when compared to the HFS group, suggesting that PEJ inhibited pancreatic lipase activity both in vitro and in vivo. In the PEJ groups, the levels of total cholesterol, LDL and NEFA were reduced and those of HDL increased. The hepatic concentration of TAG was also reduced by PEJ. Energy expenditure and UCP1 expression were higher for both supplemented groups when compared to the HFS group. PEJ positively altered the intestinal microbiota and the analysis of metabolites showed that animals treated with PEJ had different metabolomic profile. Together, these results demonstrated that polyphenols from jaboticaba may be used as adjuvants against obesity and associated health problems.